Solubilidade de calcários em extratores químicos - Bellingieri, P.A. [UNESP]; Alcarde, J.C. [UNESP]; Souza, E.C.A.de [UNESP] (Universidade de São Paulo (USP), Escola Superior de Agricultura, 1988)
A solubilidade de quatro calcários agrícolas, dois sedimentares e dois metamórficos, divididos em quatro frações granulométricas, foi estudada em dois extratores químicos (soluções de ácido clorídrico e de ácido acético), em variadas condições, com o objetivo de avaliar a eficiência desses materiais através desse critério. Os resultados obtidos, comparados com os ensaios de incubação com solos, mostraram que para a pretendida avaliação, os extratores não se prestam para avaliar os calcários agrícolas, visto que não há correlação entre a solubilidade, expressa em equivalente de CaCO3, e a eficiência mostrada nos ensaios de incubação com solos.

The solubility of four limestones (sedimentar and methamorfic) separated in four granulometric fractions were studied using two chemical extractants (solutions of hydrochloric and acetic acids), under different conditions, with the objective of evaluating the efficiency of these materials by means of that criterion. The results, compared with others obtained by incubation with soils, showed that the chemical extractants can not be used to evaluate the agricultural limestones because there was no correlation between solubility, expressed in terms of equivalent of CaCO3, and the efficiency showed in the soil incubation study.
Solubility of limestones in chemical extractants
Keywords: calcário agrícola; solubilidade; extrator químico; Agricultural limestone; solubility; chemical extractant